BITCOIN IN CENTRAL BANK RESERVES: A NEW DIMENSION OF THE US-CHINA POWER STRUGGLE - Hudima, Tetiana; Kamyshanskyi, Vladyslav (Socio-economic relations in the digital society, 2025)
The accelerating geopolitical rivalry between major powers has renewed interest in diversifying central bank reserves. Traditionally dominated by the US dollar and gold, global reserve composition is now being reconsidered amid de-dollarization trends and the growing relevance of crypto assets – particularly Bitcoin. This study examines the rationale, risks, and strategic implications of incorporating Bitcoin into sovereign reserve portfolios, with a focus on the financial confrontation between the United States (US) and the People’s Republic of China (China).Adopting an interdisciplinary approach, the paper integrates macroeconomic, legal, and geopolitical analysis. It explores the United States’ gradual institutional accommodation of Bitcoin, culminating in the 2025 establishment of a Strategic Bitcoin Reserve, contrasted with China’s prohibitive stance and promotion of the centralized digital yuan (e-CNY). The study further analyzes the legal instruments, regulatory strategies, and infrastructural controls through which the US exerts influence over crypto markets, including indirect market interventions and custodial frameworks.Findings indicate that, despite high volatility and limited adoption, Bitcoin is increasingly perceived as a strategic hedge by states seeking to reduce dependence on traditional financial hegemony. While its formal inclusion in reserves remains marginal and politically constrained, its symbolic and geopolitical utility is growing – particularly for sanctioned or financially isolated economies.The article concludes that Bitcoin’s role in global finance may expand under specific conditions: market stabilization, regulatory convergence, and persistent geopolitical fragmentation. To support structured evaluation, the paper introduces two novel analytical concepts – the Sovereign Crypto Reserve Readiness Index (SCRRI) and the Bitcoin Reserve Exposure Threshold (BRET), which together provide a framework for assessing both institutional feasibility and risk-adjusted limits for sovereign Bitcoin integration.
Keywords: Bitcoin; central bank reserves; geopolitical rivalry; de-dollarization; digital gold; cryptocurrency regulation; economic law; monetary sovereignty; legal framework